2012
DOI: 10.1128/mcb.06301-11
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function of p38-Regulated/Activated Kinase in Endothelial Cell Migration and Tumor Angiogenesis

Abstract: The p38 mitogen-activated protein kinase (MAPK) pathway has been implicated in both suppression and promotion of tumorigenesis. It remains unclear how these 2 opposite functions of p38 operate in vivo to impact cancer development. We previously reported that a p38 downstream kinase, p38-regulated/activated kinase (PRAK), suppresses tumor initiation and promotion by mediating oncogene-induced senescence in a murine skin carcinogenesis model. Here, using the same model, we show that once the tumors are formed, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 50 publications
4
70
1
Order By: Relevance
“…MAPKAPK5 is a protein kinase that functions downstream of p38 in the MAPK pathway, a mediator of infl ammatory response ( 36 ). Studies have shown that it is active in endothelial cells, where it mediates EC migration and angiogenesis ( 37 ). Little is known regarding a role for TCTN1 in cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKAPK5 is a protein kinase that functions downstream of p38 in the MAPK pathway, a mediator of infl ammatory response ( 36 ). Studies have shown that it is active in endothelial cells, where it mediates EC migration and angiogenesis ( 37 ). Little is known regarding a role for TCTN1 in cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinases (MAPKs), including extracellular signalregulated kinase 1/2 (ERK1/2), c-Jun NH2-terminal kinase (JNK), and p38, are a family of central signaling molecules that respond to numerous stimuli and are known to participate in cell survival and death decisions (Hardie 2011;Kanaji et al 2013). Moreover, the activation of JNK and p38 MAPK phosphorylation can induce apoptotic responses in endothelial cells (Yoshizuka et al 2012). Evidence has been demonstrated that reactive oxygen species (ROS) can activate JNK/p38 MAPK signaling and trigger subsequent apoptosis (Ong et al 2015;Tormos et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Yoshizuka and collaborators showed that MK5 mediates cytoskeletal reorganization during migration of endothelial cells in response to vascular endothelial growth factor (VEGF) and, maybe, additional factors secreted by the skin tumor epithelium ( Figure 5 ; Yoshizuka et al , 2012a ). VEGF binds predominantly VEGF receptor 2 (VEGFR2), and this triggers MK5 Thr-182 phosphorylation through a cascade involving the p38 MAPK isoforms α and β , but not ERK3 and ERK4.…”
Section: Mk5 and Angiogenesismentioning
confidence: 99%
“…The exact mechanism for MK5-mediated FAK phosphorylation and activation remains to be solved. A striking finding by Yoshizuka and colleagues is that VEGF-induced HSP27 phosphorylation in human vascular umbilical veil endothelial cells was not mediated by MK5 because VEGF-provoked HSP27 phosphorylation was not affected in MK5-depleted cells (Yoshizuka et al , 2012a ). Thus, although HSP27 is a genuine substrate of MK5, and MK5 can be activated by p38 MAPK (reviewed in Shiryaev and Moens , 2010 ), VEGF-induced HSP27 phosphorylation occurs in a MK5-independent manner.…”
Section: Mk5 and Angiogenesismentioning
confidence: 99%